A gendered conjoint analysis of tilapia trait preference rankings among urban consumers in Zambia: evidence to inform genetic improvement programs - Murphy, Seamus; Cole, Steven M.; Kaminski, Alexander M.; Charo-Karisa, Harrison; Basita, Rose Komugisha; McDougall, Cynthia; Kakwasha, Keagan; Mulilo, Tabitha; Rajaratnam, Surendran; Mekkawy, Wagdy (Elsevier, 2024)
Zambia has experienced a rise in per capita fish supply in recent years due in part to growing domestic aquaculture production and expanding import markets that supply farmed Nile tilapia to mostly urban markets. While urban consumers enjoy a wide variety of local fish species, including wild-caught native tilapia, little is known regarding the consumer preferences for farmed tilapia traits. Understanding aquaculture consumer markets is needed, including more detailed evidence of differences in tilapia trait preferences between women and men of differing socioeconomic backgrounds. Such data may add value to current and future genetic improvement programs, inform the design of domestic production systems and aquaculture marketing campaigns, and improve the food and nutrition security potential of the sector. This study assessed consumer preference rankings of farmed tilapia traits in four major urban sites in Zambia in 2018. Women and men consumers of different socioeconomic status (SES) participated in the study (N = 313). Using a pairwise ranking method and multi-criteria survey tool, consumers made a choice between values of different morphometric traits: total body weight, length, width, and height, skin colour, and head and tail sizes. Men reported a stronger preference for traits that were ranked higher overall by the sample, including larger body weight (p < 0.001), darker skin colour (p < 0.05), and taller body height (p < 0.05). Women reported stronger preferences for traits that were ranked lower overall, including shorter body height (p < 0.01) and smaller body weight (p < 0.001). Controlling for several covariates believed to influence consumer trait preferences for farmed tilapia (e.g., SES, age, educational level, and household size), nonparametric regression analysis revealed strong consumer preferences by men for thicker body width (p < 0.05), larger body weight (p < 0.001), and taller body height (p < 0.05). Consumers of lower SES had a stronger preference for darker skin colour than consumers of middle SES (p < 0.05). These findings confirm existence of differences in consumer preferences for farmed tilapia traits in urban Zambia and should be considered in genetic improvement programs. Fish breeding thus should be more gender-responsive and pro-poor. Differences suggest limitations in genetic innovations to meet the needs of diverse consumer groups, requiring complementary production and marketing interventions within the aquaculture industry.